Black males and intercollegiate athletics an exploration of problems and solutions - Bennett, Robert A. (Diversity in higher education ;, 2015)
This book is needed to help guide the conversation around ways to address the great disparities that impact African American males in intercollegiate athletics. In particular, scholars and practitioners have grappled with issues surrounding the climate and opportunities presented to African American males as student-athletes and coaches. Yet, there has not been a single text dedicated to identifying issues pertaining to the success and pitfalls of Black males not just as student-athletes, but also as coaches, administrators, and academic support staff in intercollegiate athletics. By addressing such topics as the economic realities of athletic competition, academic achievement, mental health, job opportunities, and identity, a new discourse will emerge on the role of African American males in college sports. This work will revisit old issues and explore the new complexities surrounding Black males in the realm of athletics in higher education with the purpose of improving their plight.